Indirect interaction of 13C nuclear spins in diamond with NV centers: simulation of the full J-coupling tensors - Nizovtsev, Alexander; Pushkarchuk, Aliaksandr; Kuten, Semen; Michels, Dominik; Lyakhov, Dmitry; Kargin, Nikolai; Kilin, Sergei (Frontiers in Quantum Science and Technology, 2024)
Recent experiments on the detection, imaging, characterization and control of multiple 13 C nuclear spins,as well as of individual 13 C-13 C dimers in diamond using a single nitrogenvacancy (NV) center as a sensor, along with the impressive progress in increasing, up to sub-Hertz, the spectral resolution of such sensor, have created a request for detailed knowledge of all possible spin interactions in the studied systems. Here, we focus on the indirect interaction (J-coupling) of 13 C nuclear spins in diamond,which was not previously taken into account in studies of NV centers. Using two different levels of the density functional theory (DFT), we simulated the full tensors n JKL (K, L = X, Y,Z), describing n-bond J-coupling of nuclear spins 13 C in H-terminated diamond-like clusters C10H16 (adamantane) and C35H36, as well as in the cluster C33[NV − ]H36 hosting the negatively charged NV -center. We found that, in addition to the usually considered isotropic scalar n J-coupling constant, the anisotropic contributions to the n J-coupling tensor are essential. We also showed that the presence of the NV center affects the J-coupling characteristics, especially in the case of 13 C-13 C pairs located near the vacancy of the NV center.